Uterine arteriovenous malformation - Alessandrino, F. (Springer International Publishing AG, 2013)
Uterine arteriovenous vascular malformations (UAVM) are uncommon vascular diseases, occurring during reproductive age. Patients affected by UAMVs usually present with recurrent pregnancy loss or menorrhagia. Initial evaluation of UAVMs is made with ultrasonography (US) and US-Doppler. Magnetic resonance is used when a UAMV is suspected at US. Treatment can be surgical (hysterectomy or surgical removal of AVM), or with selective uterine arterial embolization. We report a case of UAMV, from its clinical signs to diagnostic confirmation and subsequent treatment.